2001
DOI: 10.1111/1467-954x.00254
|View full text |Cite
|
Sign up to set email alerts
|

Language and Power in Japanese Transplants in Scotland

Abstract: Previous research into Japanese owned and managed enterprises in western countries has been alert to problems in cross-cultural communication but there has been little research into the linguistic patterns accompanying these activities. This study of seven such plants in Scotland illustrates key features of the linguistic patterns evident in them. Forms of pidgin develop in co-operative working environments but unusually they are based on the language of the formal subordinates, local English speaking managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Japanese managers generated resentment among their subordinates as a result of using the Japanese language at various times to exclude them from discussions on work-related matters and decision making (Wright, Kumagai, and Bonney 2001). As other studies have found, this is by no means an isolated example: whether by deliberate gatekeeping or not, language can be a powerful force generating a sense of exclusion from key information processes and ultimate decision making for those without the appropriate language skills, and producing almost an inevitable resentment about the managers and managerial processes.…”
Section: Social Exclusion and Powermentioning
confidence: 99%
“…Japanese managers generated resentment among their subordinates as a result of using the Japanese language at various times to exclude them from discussions on work-related matters and decision making (Wright, Kumagai, and Bonney 2001). As other studies have found, this is by no means an isolated example: whether by deliberate gatekeeping or not, language can be a powerful force generating a sense of exclusion from key information processes and ultimate decision making for those without the appropriate language skills, and producing almost an inevitable resentment about the managers and managerial processes.…”
Section: Social Exclusion and Powermentioning
confidence: 99%
“…Researchers typically looked at interactions in which a native English-speaking group interacted with non-native speakers (e.g. San Antonio, 1987;Wright, Kumagai, & Bonney, 2001;Harzing & Feely, 2008;Lauring, 2008) or studied the overseas subsidiaries of Nordic companies (Andersen & Rasmussen, 2004;BarnerRasmussen & Björkman, 2005, 2007, Lauring, 2008. Even the few studies that included a larger number of MNCs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Looking at what tongues actually mean and do to people requires methodological approaches beyond the study of documents (Kankaanranta, REBUILDING BABEL 8 2006) or policy and interviews (Fredriksson, Barner-Rasmussen, & Piekkari, 2006;Wright et al, 2001). This could, for example, be achieved by examining linguistic tensions in society at large (Harzing & Feely, 2008).…”
Section: The Plurilingual Organizations Literaturementioning
confidence: 99%